Oratorios, Theatre Royal, Drury-Lane, Friday March 1,1816 - Theatre Royal, Drury Lane (London, England):::Creator:::::::::::: (London; Theatre Royal ; Lowndes and Hobbs, printers, 2020)
Handbill listing works to be performed at the Theatre Royal, London, on March 1, 1816 (including Beethoven's Mount of Olives, op. 86, and Wellington's Victory, op. 91) and names of performers.